The Pathogenic Sphingolipid Psychosine is Secreted in Extracellular Vesicles in the Brain of a Mouse Model of Krabbe Disease. (March 2022) - Reiter, Cory R.; Rebiai, Rima; Kwak, Angelika; Marshall, Jeff; Wozniak, Dylan; Scesa, Giusepe; Nguyen, Duc; Rue, Emily; Pathmasiri, Koralege C.; Pijewski, Robert; van Breemen, Richard; Cologna, Stephanie; et al.
Psychosine exerts most of its toxic effects by altering membrane dynamics with increased shedding of extracellular vesicles (EVs). In this study, we discovered that a fraction of psychosine produced in the brain of the Twitcher mouse, a model for Krabbe disease, is associated with secreted EVs. We evaluated the effects of attenuating EV secretion in the Twitcher brain by depleting ceramide production with an inhibitor of neutral sphingomyelinase 2, GW4869. Twitcher mice treated with GW4869 had decreased overall EV levels, reduced EV-associated psychosine and unexpectedly, correlated with increased disease severity. Notably, characterization of well-established, neuroanatomic hallmarks of disease pathology, such as demyelination and inflammatory gliosis, remained essentially unaltered in the brains of GW4869-treated Twitcher mice compared to vehicle-treated Twitcher controls. Further analysis of Twitcher brain pathophysiology is required to understand the mechanism behind early-onset disease severity in GW4869-treated mice. The results herein demonstrate that some pathogenic lipids like psychosine may be secreted using EV pathways. Our results highlight the relevance of this secretory mechanism as a possible contributor to spreading pathogenic lipids in neurological lipidoses.